Formation of Creative Abilities in Students of Pedagogical University - Roman Horbatiuk (Pedagogical Discourse, 2013)
The model of creative abilities forming in the future computer profile’s engineer-teachers is determined and its basic components are also defined in this article. System approach to the development of the model of students’ creative abilities formation provides for personal, functional, content-processual and technological components of formation of professionalism of the future specilists.On the basis of marked out conformities and principles scientific-methodical conditions, which provide effectiveness of the future computer profile’s engineer-teachers’ creative abilities formation. It is established that the efficiency of the proposed model is achieved on the basis of  of inter-related components: target, stimulative-motivational, informative, project-organized, processual-actional, and estimation-criterion.